Experimental Study of the Development of Soil Microstructure under the Electroosmosis Dewatering Process - Yimin Liu; Lingwei Zheng; Shaohua Rao (Advances in Materials Science and Engineering)
Several laboratory experiments using scanning electron microscopy and mercury intrusion porosimetry were conducted to study the development of soil microstructure during electroosmosis dewatering process. The test results indicate that the moisture content in different treating areas shows remarkable temporal difference; the reasons could be attributed to the distance to the drainage outlets and the treatment duration. On a microscopic level, the affected pore sizes are mainly 0.01–1 and 1–10 μm, and their proportions start to vary when the moisture content reaches the liquid limit. The total volume for pores in anodic soil decreases nearly 50% after the first 20% of total drainage water is exported and is not linearly related to the amount of discharged water. The surface of the soils becomes smoother, and clay particle connection changes from edge-to-edge to face-to-face. Pores are hard to be observed at the end of the process.